1992
DOI: 10.1177/0011000092204004
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Neuropsychological Training Into a Counseling Psychology Curriculum

Abstract: This article presents a rationale for the integration of training in neuropsychology into a counseling psychology curriculum. This rationale is discussed against the historical development of the counseling psychology specialty and the current practice of counseling psychologists. A means of integrating training in neuropsychology is proposed that allows this training to serve as a potential means of providing a unifying focus for various didactic and clinical components of the doctoral curriculum. Finally, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Calls for counselling psychology to align more closely with other health care professions (Alcorn, 1991;Altmaier, 1991, Harris, 1991, including neuropsychology (Agresti, 1992;Larson, 1992), and child clinical psychology (Kaczmarek and Wagner, 1994), encourage an additional kind of elasticity in the eld's identity that pose further challenges to the integrity and coherence of its core moorings. The consequence, as Fretz (1980, p. 9) noted wryly, is that 'Counselling psychology, it seems, is in the eye of the beholder'.…”
Section: Core Identity Commitmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calls for counselling psychology to align more closely with other health care professions (Alcorn, 1991;Altmaier, 1991, Harris, 1991, including neuropsychology (Agresti, 1992;Larson, 1992), and child clinical psychology (Kaczmarek and Wagner, 1994), encourage an additional kind of elasticity in the eld's identity that pose further challenges to the integrity and coherence of its core moorings. The consequence, as Fretz (1980, p. 9) noted wryly, is that 'Counselling psychology, it seems, is in the eye of the beholder'.…”
Section: Core Identity Commitmentsmentioning
confidence: 99%
“…This was the area of neuropsychological assessment …Mˆ3:81 †, a prediction that is supported by the work of Larson (1992) and Agresti (1992), and a wide spectrum of scholars and practitioners who support the development of counselling psychology more broadly within the elds de ned by the allied health professions (see Alcorn, 1991;Altmaier, 1991). Out of the ve areas of assessment studied (objective, projective, neuropsychological, vocational and behavioural), only one was nominated for substantially greater future attention.…”
Section: Professional Trainingmentioning
confidence: 99%
“…Although informative, the Solomon et al findings are out of date, particularly in light of changes in the field of counseling psychology. During the past decade, the number of APA-accredited counseling psychology programs has almost doubled (APA, 1994), neuropsychology has emerged as one of the most rapidly growing specialty areas, and practicing counseling psychologists have broadened their scope of activities to include neuropsychological assessment and intervention (Agresti, 1992;Kemp, 1992;Larson, 1992).…”
mentioning
confidence: 99%
“…One prominent finding was that there were two distinct periods of publications. The first period consisted of eight articles from a special edition of the SAGE journal The Counseling Psychologist in 1992, which focused on exploring the growing involvement of counseling psychology within neuropsychology (Agresti, 1992;Corazzini, 1992;Kemp, 1992;Larson, 1992;Larson & Agresti, 1992;Malec, 1992;Paulsen, 1992;Woody, 1992). This set of articles greatly influenced the third theme, Integrating Neuropsychology.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of authors suggested that this fear is unfounded and unnecessary and that neuroscience is part of taking a pragmatic, holistic perspective of clients (Goss, 2015;Rizq, 2007). Counseling psychologists can maintain their core professional identity when diversifying into other areas, including neuroscience (Agresti, 1992;Corazzini, 1992;Larson & Agresti, 1992;Paulsen, 1992) and neuroscience more broadly (Goss, 2015).…”
Section: Discussionmentioning
confidence: 99%